A study of vegetative and reproductive development in 'Clementine' Citrus reticulata Blanco - Cook, Nigel Colin (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1992.